The Devastating Ramche Landslide (Rasuwa) and the Future of Polchet Residents - Ghimire, T; Paudel, LP; Pant, B (Journal of Nepal Geological Society, 2008)
The Ramche landslide is located at the 36-km sector of the Trisuli-Dhunche motor road in the Rasuwa district. According to the local residents, it was first activated in 1983 and reactivated at the night of 14 August 2003 killing 23 army men on the site and injuring many others. Since then the landslide is active. Geologically, the landslide is at the southern limb of the Kuncha-Gorkha anticlinorium formed by alternating bands of metasandstones and chlorite-phyllite. Up to 30 m thick loosely packed colluvium (fine-grained sand to huge boulders) is filled in a wedge-shaped structure formed by joint and foliation. Bedrock is exposed both at the crown and toe of the slide. The motor road passes across the slide. Diversion of stream water over the colluvium for irrigation, increased infiltration due to excavation for making road together with sealing effect of highly impermeable Kuncha phyllites at the base of the colluvium has increased pore water pressure in the soil. Reduced soil strength due to pore water pressure together with vibration of land due to heavy traffic have caused the debris to flow downslope on the rock surface. The slide seems more active in the monsoon time and relatively stable in the winter. The movement rate is more than a meter per year. It has developed several cracks on the surface causing collapse of houses. The slide has put more than 100 people and their cattle living in 16 houses of Polchet village and at immediate risk. Further, two high-tension poles of Chilime hydropower and the 36-km sector of the Trisuli- Dhunche road have been destabilized by the slide. So far, there have been no efforts to stabilize the slide and protect the life of Polchet residents. Preliminary, observation shows that effective drainage control and abandoning rice cultivation may help in reducing pore water pressure and stabilize the landslide. However, a detailed study is needed before taking any preventive measures. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.27